Modelling the effects of temperature change on the dynamics of tsetse flies and trypanosomiasis disease transmission - Mthombothi, Zinhle Emily (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.